2022
DOI: 10.1177/0271678x221124656
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasomotor reactivity across the continuum of subjective cognitive impairment, amnestic mild cognitive impairment and probable Alzheimer's dementia: A transcranial Doppler and PET/MRI study

Abstract: Cerebrovascular dysfunction has been suggested as a physiomarker of Alzheimer's disease (AD)-associated neuronal degeneration, but the underlying mechanisms are still debated. Herein cerebral vasomotor reactivity (VMR, breath-hold index: BHI), metabolic activity (lobar SUVs, FDG PET MRI), amyloid load (Centiloid score, Flutemetamol PET MRI), hemispheric cortical thickness, white matter lesion load and cerebral blood flow (ASL) were studied in 43 consecutive subjects (mean age: 64 years, female 13), diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Our findings add to the observations of a decreased cerebrovascular reactivity in MCI and AD patients as measured by transcranial doppler sonography 41 45 and by BOLD MRI with CO 2 as vasodilatory stimulus. 46 48 These studies may also have been detecting changes related to comorbid CAA although it was not mentioned specifically in these studies.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings add to the observations of a decreased cerebrovascular reactivity in MCI and AD patients as measured by transcranial doppler sonography 41 45 and by BOLD MRI with CO 2 as vasodilatory stimulus. 46 48 These studies may also have been detecting changes related to comorbid CAA although it was not mentioned specifically in these studies.…”
Section: Discussionsupporting
confidence: 82%
“… 51 , 52 , 53 , 58 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 75 , 77 , 78 , 80 , 81 , 83 , 86 , 87 , 91 The remaining 18 studies were prospective or retrospective cohort studies. 54 , 55 , 56 , 57 , 59 , 62 , 72 , 73 , 74 , 76 , 79 , 82 , 84 , 85 , 92 , 93 , 94 , 95 In 203 patients with leukoaraiosis, Bian et al 91 demonstrated that patients exhibiting more severe white matter hyperintensities (Fazekas grades II and III) had a significantly reduced cerebrovascular reactivity compared with those with lower severity. In another larger cohort study, Staszewski et al 58 reported that in 120 subjects, the lowest tertile of cerebrovascular reactivity had a 19‐fold greater likelihood of having cSVD compared with the highest tertile.…”
Section: Resultsmentioning
confidence: 99%